Development of a Lateral Flow Highway: Ultra-Rapid Multitracking Immunosensor for Cardiac Markers - Byzova, Nadezhda A. (Sensors (Basel), 2019)
The integration of several controlled parameters within a single test system is experiencing increased demand. However, multiplexed test systems typically require complex manufacturing. Here, we describe a multiplexed immunochromatographic assay that incorporates a conventional nitrocellulose membrane, which is used together with microspot printing, to construct adjacent microfluidic “tracks” for multiplexed detection. The 1 mm distance between tracks allows for the detection of up to four different analytes. The following reagents are applied in separate zones: (a) gold nanoparticle conjugates with antibodies against each analyte, (b) other antibodies against each analyte, and (c) antispecies antibodies. The immersion of the test strip in the sample initiates the lateral flow, during which reagents of different specificities move along their tracks without track erosion or reagent mixing. An essential advantage of the proposed assay is its extreme rapidity (1–1.5 min compared with 10 min for common test strips). This assay format was applied to the detection of cardiac and inflammatory markers (myoglobin, D-dimer, and C-reactive protein) in human blood, and was characterized by high reproducibility (8%–15% coefficient of variation) with stored working ranges of conventional tests. The universal character of the proposed approach will facilitate its use for various analytes.